ANALISIS RESPON HARGA DAN KESAMAAN GERAK (COMOVEMENT) PADA PERUBAHAN INDEKS DI BURSA EFEK INDONESIA - , Abdur Rafik ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study is to examine the presence of price response and comovement in the context of stocks addition and stocks deletion in Indonesia. Demand-based hypothesis of price response assumes that there will be no price change of stocks that added to and deleted from index due to irrelevant information. The other hypothesis, namely information-based hypothesis, assumes that index change contains relevant information and predicts a positive response to added stocks and a negative response to deleted stocks. In another side, behavioral finance hypothesis predicts the presence of comovement to stocks added to the index due to trading bias of investors, and vice versa. This prediction againsts traditional finance hypothesis that assumes the presence of comovement due to fundamental correlation. Event study methodology was used to examine the price respose and Barberis et al. (2005) methodology was adopted to prove comovement. The units of analysis were LQ45, Jakarta Islamic Index (JII), Kompas 100, Pefindo 25, Bisnis 27, and SRI-KEHATI. Observation periods were different between indexes. The entire observation period was started from the second semester of 2003 to the second semester of 2012. The result of price response test confirmed that there wasis no positive price response to added stocks and there was no negative price response to deleted stock. Price response patterns did not support information-based hypothesis, and more consistent with the predictions of demand-based hypothesis. Price response patterns between the indexes were insensitive and even reverse i.e positive for deleted stocks and negative for added stocks. This reverse pattern was able to be explained by the level of liquidity and fundamental characteristics of stocks. Positive return on stock deletion was positively associated with high liquidity, high debt levels, and low growth opportunities. While negative return on stock addition was positively associated with low liquidity, low debt levels, and high growth opportunities. These results seem to confirm the benefits of premium value-based investment strategy in Indonesian context. In another sife, patterns of comovement were found in stock added to the index, and vice versa. The result supported the behavioral finance hypothesis related to presence of sentiment in stock addition (deletion) to (from) index. Comovement was able to be explained by habitat and category view of Barberis et al. (2005). Comovement patterns between indexes were sensitive to index category. Comovement in addition was found in Pefindo 25 dan JII, while the opposite movement was found in LQ45, Pefindo 25, and Bisnis 27. The result implied that comovement was not associated with the presence of positive price response, and vice versa.